Cognitive and emotional statements as components of reciprocal interaction in network thinking - Denis F. Dautov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Working in the world of the 21st century requires ever closer cooperation, more and more people. At the same time, paradoxically, the people of this society are increasingly striving for independence and feel lonely, despite the increased possibilities of digital technologies that greatly facilitate information interaction. All this could not but affect human thinking, which, together with network technologies, was forced to change significantly, turning into network thinking. As thinking changes, so does the interaction between people. To study this interaction, a study was conducted to analyze the components of reciprocity in network thinking. The method used in obtaining primary results was content analysis. Mathematical processing of the obtained data was carried out by means of multivariate analysis of variance. The study determined the parameters of the initial conditions of network thinking that affect various forms of reciprocity, as well as emotional and cognitive statements. Combinations of conditions in the greatest and least degree influencing the quantitative and qualitative component of interaction in solving mental problems are revealed. The influence of various forms of reciprocity on emotional and cognitive statements realized in the process of network thinking by participants in problem solving has been established. Combinations of two forms of reciprocity are determined that contribute to a change in the number of emotional and cognitive statements. Fundamental differences in the influence of various forms of reciprocity on utterances in the process of joint mental activity are revealed. The results obtained as a result of the study can be used to assess the features of interdependent interaction in the implementation of network thinking and its correction by changing the initial conditions for the implementation of mental activity.